Modeling the Bioavailability of Nickel and Zinc to Ceriodaphnia dubia and Neocloeon triangulifer in Toxicity Tests with Natural Waters. (21st September 2021) - Besser, John M.; Ivey, Chris D.; Steevens, Jeffery A.; Cleveland, Danielle; Soucek, David; Dickinson, Amy; Van Genderen, Eric J.; Ryan, Adam C.; Schlekat, Chris E.; Garman, Emily; Middleton, Ellie; Santore, Robert
Abstract: We studied biotic ligand model (BLM) predictions of the toxicity of nickel (Ni) and zinc (Zn) in natural waters from Illinois and Minnesota, USA, which had combinations of pH, hardness, and dissolved organic carbon (DOC) more extreme than 99.7% of waters in a nationwide database. We conducted 7‐day chronic tests with Ceriodaphnia dubia and 96‐hour acute and 14‐day chronic tests with Neocloeon triangulifer and estimated median lethal concentrations and 20% effect concentrations for both species. Toxicity of Ni and Zn to both species differed among test waters by factors from 8 (Zn tests with C. dubia ) to 35 (Zn tests with N. triangulifer ). For both species and metals, tests with Minnesota waters (low pH and hardness, high DOC) showed lower toxicity than Illinois waters (high pH and high hardness, low DOC). Recalibration of the Ni BLM to be more responsive to pH‐related changes improved predictions of Ni toxicity, especially for C. dubia . For the Zn BLM, we compared several input data scenarios, which generally had minor effects on model performance scores (MPS). A scenario that included inputs of modeled dissolved inorganic carbon and measured Al and Fe(III) produced the highest MPS values for tests with both C. dubia and N. triangulifer . Overall, the BLM framework successfully modeled variation in toxicity for both Zn and Ni across wide ranges of water chemistry in tests with both standard and novel test organisms. Environ Toxicol Chem 2021;40:3049–3062. © 2021 SETAC. This article has been contributed to by US Government employees and their work is in the public domain in the USA.